KAJIAN ARSITEKTUR ISTANO SILINDUANG BULAN DENGAN ISTANO BASA PAGARUYUNG KABUPATEN TANAH DATAR SUMATERA BARAT - YORHA ASRIA PUTRI, Drs. Syafwan, M.Si., Ir. Drs. Heldi, M.Si., Ph,.D. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The0architecture0of0Istano0Silinduang0Bulan0and0Istano0Basa0Pagaruyung0cannot0be0separated0from0the0vernacular0architectural0structure0of0the0gadang0house0or0the traditional0Minangkabau0house. Which0has0different0forms0and0functions, 0but0many of the local and non-local people do not understand even to the wrong perception about the two Istano or the gadang house, many of the people cause differences related to the problem of the form and function of the two Istano for example: in0the0section0basic0framework, main elements, and supporting elements that contain social values of the life of the Minangkabau people. The purpose of the study will explain the differences in the form of architectural structures and the structural functions of the two Istano. This research is located in Nagari Pagaruyung Batusangkar precisely on Jl. Sutan Alam Bagagarsyah, Tanjung Emas, Tanah Datar District, West Sumatra. The research method used is a qualitative research with a descriptive approach, research conducted with observations of spaciousness, interviews, and gathering documentation. Data collection by reducing data, presenting data and describing the findings. The0results0of0the0study0on0Istano0site0structure0and0floor0plan, front and rear view, left and right side view, inside appearance, as well as differences in form and function in the architectural structure of the two Istano.Keywords: Architecture, Form, Function, Istano.